2017
DOI: 10.1021/acs.biomac.7b01109
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonically Enhanced Galactoxyloglucan Endowed Gold Nanoparticles Exposed Tumor Targeting Biodistribution Envisaged in a Surface-Enhanced Raman Scattering Platform

Abstract: Biopolymer-capped gold nanoparticles (AuNPs) were perceived for tracing biodistribution in a solid tumor mice through surface-enhanced Raman scattering (SERS) fingerprinting. In this strategy, a robust and ecofriendly green chemistry approach was adopted to construct galactoxyloglucan (PST001) endowed AuNPs (PST-GNPs) with cancer-cell-selective toxic nature and excellent biocompatibility. Plasmonically enhanced light-scattering properties facilitated PST-GNPs to be a superior SERS substrate with high Raman sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In addition to its role in maintaining organism homeostasis, the immune system also plays a crucial role in the modulation of ovarian function, as it regulates ovarian development, follicular maturation, ovulation and the formation of the corpus luteum [127][128][129][130][131]. In recent years, studies have also shown that immunosuppressive mechanisms and chronic inflammation play an important role in the pathogenesis of ovarian premature aging.…”
Section: Immunosuppressive Mechanisms and Chronic Inflammationmentioning
confidence: 99%
“…In addition to its role in maintaining organism homeostasis, the immune system also plays a crucial role in the modulation of ovarian function, as it regulates ovarian development, follicular maturation, ovulation and the formation of the corpus luteum [127][128][129][130][131]. In recent years, studies have also shown that immunosuppressive mechanisms and chronic inflammation play an important role in the pathogenesis of ovarian premature aging.…”
Section: Immunosuppressive Mechanisms and Chronic Inflammationmentioning
confidence: 99%
“…To gather information about the mechanistic action of TTNV, various apoptosis assays were performed on cells and spheroids as described before. [ 19,49 ] Atomic force microscopy was also employed to visualize the morphological changes, and eventually, SERS was utilized to decipher the apoptotic molecular changes in a label‐free fashion. The influence caspases were determined using caspase profiling kit (Clontech, Mountain View, CA) and cell cycle analysis was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor reduction experiments were initially performed with DLA ascetic tumor‐bearing Swiss albino mice with three different groups (Scheme S1, Supporting information) as described before. [ 19,42,49 ] Later, the studies were done with EAC solid tumor‐bearing Swiss albino syngeneic models after ip injections (Scheme S2, Supporting information) and sacrificed on day 32. Finally, the CSC‐targeting capacity of TTNV was illustrated on the xenograft of human CSC‐rich tumors in immunocompromised mice.…”
Section: Methodsmentioning
confidence: 99%
“…Non‐invasive imaging of cancer cells using SERS was carried out and ex vivo biodistribution of solid tumor gave the evidence that other organs remained unaffected [100,101] . Gold mesoporous silica hybrid and hollow gold NPs (Figure 6B) decorated with various cancer biomarkers were also investigated for the SERS imaging capability.…”
Section: Surface Enhanced Raman Scatteringmentioning
confidence: 99%